Strategi Manajemen Lingkungan (Eco-Pesantren): Studi Lapangan Pengelolaan Sanitasi dan Kebersihan di Pondok Pesantren Anwarul Huda Malang - Wahyudi Widodo (ALSYS, 2026)
Although environmental management in pondok pesantren, particularly in the aspects of sanitation and cleanliness, is an important necessity, its implementation remains challenging due to the large number of santri and the density of daily activities. This study aims to analyze the Eco-Pesantren-based environmental management strategy in managing sanitation and cleanliness at Pondok Pesantren Anwarul Huda Malang. This study used a qualitative method with a field study approach through observation, in-depth interviews, and documentation involving the pesantren leader, administrators, and santri. The results showed that the environmental management strategy was implemented in a planned and integrated manner through the functions of planning, implementation, supervision, and evaluation. Sanitation and cleanliness management is not only technical in nature, but is also internalized as a pesantren value and culture through written policies, active participation of santri, and an educational supervisory approach. The Eco-Pesantren program has a positive impact on environmental cleanliness, pesantren health, and the formation of santri awareness and clean living behavior. This study concludes that Pondok Pesantren Anwarul Huda Malang can serve as a model of good practice in implementing Eco-Pesantren based on sustainable environmental management.